2022
DOI: 10.3390/nu14142929
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity Effects of Aqueous Extracts of Sunbanghwalmyung-Eum in High-Fat- and High-Cholesterol-Diet-Induced Obese C57BL/6J Mice

Abstract: Sunbanghwalmyung-eum (SBH) is a traditional herbal medicine that exhibits various pharmacological properties, such as antioxidant, anti-inflammatory, and anticancer activities. In this study, we investigated the systemic anti-obesity effects of an aqueous extract of SBH in the liver, adipose, and muscle tissue from high-fat and high-cholesterol diet (HFHCD)-induced obese C57BL/6J mice. After 6 weeks of an HFHCD, the mice were continuously fed HFHC with oral administration of SBH (100 mg/kg/day), Sim (simvastat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, moderation is vital, and it's essential to combine sweet potatoes with other nutrient-rich foods and engage in regular physical activity to achieve and maintain a healthy weight. Consult a healthcare professional or a registered dietitian for personalized advice regarding individual nutrient needs and dietary restrictions [220][221][222][223][224].…”
Section: Obesitymentioning
confidence: 99%
“…However, moderation is vital, and it's essential to combine sweet potatoes with other nutrient-rich foods and engage in regular physical activity to achieve and maintain a healthy weight. Consult a healthcare professional or a registered dietitian for personalized advice regarding individual nutrient needs and dietary restrictions [220][221][222][223][224].…”
Section: Obesitymentioning
confidence: 99%
“…Abdominal obesity patients are often associated with pathological conditions such as X-syndrome and act as a powerful risk factor for early arteriosclerosis, ischemic cardiovascular disease and cerebrovascular disease [4][5][6]. The high-fat and high-sugar diet is related to cause of hyperlipidemia [7]. Kang et al reported that high-fat-induced obesity altered cognition and anxiety related behavior.…”
Section: Introductionmentioning
confidence: 99%